Sources of resistance to angular leaf spot (Phaeoisariopsis griseola) in common bean core collection, wild Phaseolus vulgaris and secondary gene pool - Mahuku, George S.; Jara, Carlos E.; Cajiao V., César Hernando; Beebe, Stephen E. (Springer, 2003)
Angular leaf spot (ALS) is one of the most devastating diseases of common bean (Phaseolus vulgaris L.) in tropical and subtropical countries. The causal fungus, Phaeoisariopsis griseola(Sacc.) Ferr. is highly variable and a diverse source of resistance genes is required to manage this disease. We evaluated a common bean core collection,primary and secondary gene pools and lines derived from inter-specific crosses of P. vulgaris and P. coccineus or P. polyanthus (secondary gene pool) for resistance to angular leaf spot. Of the 1441 accessiones in the core collection, only 2.2% were resistant to both Andean and Mesoamerican races of P. griseola, 28% were resistant only to Andean and 9% to Mesoamerican races. Of the 32 resistant accessions, 68%originated from Bolivia, Colombia,Guatemala and Mexico. More accessions from these countries should be examined for P. griseola reaction. Very few wild P. vulgaris accessions (4%), were resistant to ALS. In contrast, high levels of resistance (62%) were found in the secondary gene pool. Among the 1010 lines from inter-specific crosses, 109 lines were highly resistant. These genotypes from the primary and secondary common bean gene pools resistant to Andean and Mesoamerican races of P. griseola offer a potential for developing broad and durable ALS resistance.